Development of Thematic Based Classroom Design in Inclusive Schools - Wardana, Ludfi Arya; Rulyansah, Afib (Department of Special Education, 2019)
The purpose of this study produce design guidelines based on thematic classrooms conducted in class V inclusive schools of Tisnonegaran 1 Elementary School Probolinggo. This research and development method uses Borg & Gall which has been modified to be: (1) collection of information, (2) planning, (3) product development, (4) expert validation, (5) field trials, (6) final products. The results of the development research showed that the results of the validation of learning technology experts were 97.2% and linguists were 90.6% and the readability test was 92.8%.The conclusion of thematic-based classroom design products in inclusive schools has expert validation levels and a high level of readability so that they can be used in improving the quality of learning. Suggestions for further development can use different classes and levels.